معجزة رسول الله محمد (صلى الله عليه واله) وفق آراء المستشرقين "في دائرة المعارف الإسلامية أنموذجا" قراءة نقدية (Journal of the College of Basic Education, 2026)
Miracles are one of the arguments used by prophets and messengers to convince those who oppose, reject, and doubt the divine messages. The miracles of the Messenger of God, Muhammad (peace and blessings be upon him), the Seal of the Prophets and Messengers, were of a high standard in all their dimensions, as witnessed by his fragrant biography and recorded in authentic historical sources, including the books of interpretation that were written over the centuries of Islamic history, explaining the events and results of these miracles. Orientalists have highlighted this issue in the Encyclopedia of Islam, when they translated the Prophet Muhammad (PBUH), and they had opinions about it, which limited their opinions to the fact that the miracle of the Prophet (PBUH) was the Holy Qur’an only, without any other miracles that distinguished him and were mentioned in Islamic sources. These opinions were addressed in this research, and the falsity of their claim was demonstrated.